The combined influence of cognitions in adolescent depression: Biases of interpretation, self‐evaluation, and memory. (25th May 2018) - Orchard, Faith; Reynolds, Shirley
Abstract : Objectives: Depression is characterized by a range of systematic negative biases in thinking and information processing. These biases are believed to play a causal role in the aetiology and maintenance of depression, and it has been proposed that the combined effect of cognitive biases may have greater impact on depression than individual biases alone. Yet little is known about how these biases interact during adolescence when onset is most common. Methods: In this study, adolescents were recruited from the community ( n = 212) and from a Child And Adolescent Mental Health Service ( n = 84). Participants completed measures of depressive symptoms, interpretation bias, self‐evaluation, and recall memory. These included the Mood and Feelings Questionnaire, Ambiguous Scenarios Test for Depression in Adolescents, Self‐Description Questionnaire, and an immediate recall task. The clinically referred sample also took part in a formal diagnostic interview. Results: Individual cognitive biases were significantly intercorrelated and associated with depression severity. The combination of cognitive biases was a stronger predictor of depression severity than individual biases alone, predicting 60% of the variance in depression severity across all participants. There were two significant predictors, interpretation bias and negative self‐evaluation; however, almost all of the variance was explained by negative self‐evaluation. Conclusions: The findings support the interrelationship and additive effect of biases in explaining depression and suggest that understanding the way in which cognitive biases interact could be important in advancing methods of identification, early intervention, and treatment. Practitioner points: A combination of biases was a better predictor of depression symptom severity than individual biases. Interpretation and self‐evaluation were better predictors of depression symptom severity than recall. Negative self‐evaluation was the strongest individual predictor of depression symptom severity. Negative self‐evaluation was able to classify depressed from non‐depressed adolescents. The cross‐sectional design of the study precludes any conclusions about the potential causal role of these variables. Different tasks were used to assess different types of cognitive bias meaning that the possible linear operation along an information processing 'pathway' could not be examined.